Nasal microbiota predictors for methicillin resistant Staphylococcus colonization in critically ill children - Kathleen Zani; Joseph Hobeika; Yilun Sun; Christina Kohler; Anju Cherian; Trinity Fields; Qidong Jia; Li Tang; Nicholas D. Hysmith; Elisa B. Margolis (PLoS ONE, 2025)
Background Surveillance cultures to identify patients colonized with methicillin-resistant Staphylococcus aureus (MRSA) is recommended at pediatric intensive care unit (PICU) admission but doesn’t capture other methicillin-resistant Staphylococcus and is resource intensive. We determined the prevalence and identified nasal microbiome predictors for methicillin-resistant Staphylococcus colonization at the time of PICU admission. Study design A prospective cohort study was performed in a 20-bed pediatric intensive care unit (PICU) between 2020–2021. Anterior nares nasal swabs processed for MRSA culture, nasal microbiome and mecA+ qPCR were obtained within first five days after PICU admission. Predictive values of methicillin-resistant Staphylococcus carriage on symptoms of infection and for nasal microbiome attributes were calculated. Results A total of 5 (8.0%) of 62 patients had a nares culture positive for MRSA and 22 (35.5%) of 63 patients had methicillin-resistant Staphylococcus (MRSA or methicillin-resistant coagulase-negative Staphylococci). In univariate analysis, carriage with MRSA or MRCoNS was associated with having a fever during PICU stay. Colonization with a distinct set of microbes (including Haemophilus, Streptococcus, Prevotella and Corynebacterium sp.) was predictive of having methicillin-resistant Staphylococcus colonization. Conclusions Carriage with methicillin-resistant Staphylococcus may lead to transmission in critically ill pediatric patients. Carriage of particular nasal microbes appears to facilitate colonization with methicillin-resistant Staphylococcus.